2020
DOI: 10.1111/nicc.12527
|View full text |Cite
|
Sign up to set email alerts
|

Improving the safety and quality of the intra‐hospital transport of critically ill patients

Abstract: Background: Adverse events during patient transport are common and may threaten critically ill patients' lives.Aim: This study aimed to determine the incidence of adverse events during intrahospital transport and to obtain suggestions from critical care nurses for improving the transportation process.Design: This was a cross-sectional study.Methods: This study was carried out with 160 critical care nurses between September 2018 and January 2019. Data were collected through a semi-structured interview using a 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(46 citation statements)
references
References 40 publications
1
39
0
6
Order By: Relevance
“…It also considered the effective time to learn and modify their practice through training in ICU to improve the sense of identity and develop successful intimate relations. This finding is in the same line with Alizadeh sharafi et al (2021) (17) ,who reported that more than three quarters of the studied nurses had age less than 30 years old and more than half of them were female. Additionally, Xie et al (2020) (18) reported that the majority of studied nurses were less than 30 years old.…”
Section: Table (6): Comparison and Correlation Between Total Knowledg...supporting
confidence: 91%
“…It also considered the effective time to learn and modify their practice through training in ICU to improve the sense of identity and develop successful intimate relations. This finding is in the same line with Alizadeh sharafi et al (2021) (17) ,who reported that more than three quarters of the studied nurses had age less than 30 years old and more than half of them were female. Additionally, Xie et al (2020) (18) reported that the majority of studied nurses were less than 30 years old.…”
Section: Table (6): Comparison and Correlation Between Total Knowledg...supporting
confidence: 91%
“…The results of this survey are consistent with an ICU study in Australia, wherein 39% of adverse events were related to equipment failure 20 . Although these adverse events are not directly related to patients, they may pose potential threats to life, and can be averted by employing strategies such as the use of checklists 21,22 and development of training interventions 23,24 and technical solutions 25 . Notably, most of the tools and technologies currently used during transport have not been designed for this purpose; thus, they cannot possibly fulfil all the requirements of the transport process.…”
Section: Discussionmentioning
confidence: 99%
“…In September 2020, we passed the re‐evaluation for class III A general hospital with a high score, and the quality of IHT was recognised by experts. We believed that it can be helpful in other similar hospitals facing the same problems with IHT in which nurses are playing an important role (Alizadeh Sharafi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%